High Availability’s Implementation on the Fortigate Firewall Using SD-WAN Zone and HA Cluster Active-Passive - Fattahilah, Novandi Rizki; Nurfadila, Farah; Setiawan, Yanto (International Journal Labs, 2023)
Networks that contain sensitive data or have high-security requirements require reliable and dependable network security solutions. FortiGate Firewall, as one of the popular network security solutions, provides High Availability (HA) features that ensure network availability and reliability. This study aims to analyze the implementation of HA on FortiGate Firewall in specific scenarios, such as networks with sensitive data or networks with high-security requirements. A real-world case study is applied to evaluate the effectiveness of HA implementation on FortiGate Firewall in enhancing network reliability and security. In this research, the implementation of HA on FortiGate Firewall at PT ABC was successfully built using the PPDIOO method and deploying SD-WAN load balancing and failover configurations, along with the utilization of a high-availability cluster mechanism. The HA implementation on FortiGate proves to be an effective solution, as demonstrated in the SD-WAN Zone testing of the Source-destination SD-WAN load balancing mode, which showed effectiveness in evenly and optimally distributing traffic among multiple available links, resulting in a 93.3% reduction in downtime. Furthermore, the testing of HA cluster mode in active-passive configuration achieved a 91.8% reduction in downtime compared to the pre-HA implementation state.